Perlindungan Hukum Menurut Undang Undang No 18 Tahun 2017 Tentang Kekerasan Terhadap Pekerja Migran Indonesia - Ruminingsih Ruminingsih; Marwan Marwan (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
The availability of job opportunities in Indonesia, especially for citizens who have no skills and low education, has resulted in many Indonesians choosing to become Indonesian Migrant Workers (PMI). So many Indonesian migrant workers want to work in Saudi Arabia. Working as migrant workers is expected to improve the welfare of PMI families in Indonesia, but often PMIs in their placement countries experience acts of physical, verbal, sexual, and economic. Currently, as the number of migrant workers living abroad increases, the Indonesian Migrant Worker Protection Agency (BP2MI) is receiving more complaints from Indonesian Migrant Workers abroad. These Indonesian migrant workers complained about cases such as physical violence, wanting to be returned to Indonesia, unpaid salaries, sexual violence, and so on. In this condition, the role of the Indonesian Government is essential to implement protection for Indonesian migrant workers. Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers was enacted to increase protection for Indonesian migrant workers by the Indonesian Government. Based on existing data and news spread in the mass media, it is stated that the number of complaints due to violence against Indonesian Migrant Workers is still high, so this research wants to define the causes of violence experienced by Indonesian Migrant Workers and prove legal protection for Indonesian Migrant Workers based on the Law Number 18 of 2017. The low level of education of Indonesian Migrant Workers means that they often ignore or do not understand the departure procedures for Indonesian Migrant Workers. Legal provisions have been explained in detail in Law Number 18 of 2017, regarding the rights and obligations of Indonesian Migrant Workers; social Security; protective procedures; and the duties and responsibilities of the government, both central and regional governments. The form of protection provided is before, during, and after work. The Ministry of Manpower has developed a program called Village Care for Migrant Workers to increase legal protection for Indonesian Migrant Workers from the Village level even though the program has not been able to run optimally.